LITERATURE STUDY: THE EFFECTIVENESS OF THE USE OF E-HDW APPLICATIONS IN INCREASING THE PREVALENCE OF STUNTING - Riana, Arisma Desy; Mursyidah, Lailul (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to analyze the effectiveness of the e-HDW (Electronic Human Development Worker) application in accelerating the reduction of stunting rates in Indonesia. Method: A descriptive qualitative approach was employed, using literature studies from theses, scientific articles, and journals relevant to the research focus. The analysis was guided by Duncan’s (1985) organizational effectiveness theory, which emphasizes three indicators: goal achievement, adaptation, and integration. Results: The findings demonstrate that the e-HDW application has effectively supported stunting reduction efforts by improving data accuracy, accelerating nutrition interventions, and strengthening coordination among stakeholders. Nevertheless, challenges persist, including limited access to technology, low levels of user understanding, and technical constraints that hinder optimal implementation. Novelty: Unlike previous studies, this research applies Duncan’s organizational effectiveness framework to evaluate the e-HDW application, offering a comprehensive perspective on how digital tools contribute to public health initiatives, while underscoring the critical need for capacity building, infrastructure development, and continuous adaptation to ensure the sustainability of stunting reduction programs in Indonesia.